Dynamics in the governance of smart cities: insights from South Korean smart cities. (1st January 2023) - Lim, Yirang; Edelenbos, Jurian; Gianoli, Alberto
ABSTRACT: This paper aims to explain how the governance model changes in smart cities by using South Korea's experience as a case study. South Korean smart city development is divided into three phases according to the national master plan and maturity of smart cities. Phase 1 took place from 2008 to 2013, phase 2 extended from 2014 to 2018, and phase 3 began in 2019 and will last into 2023. The cases under consideration are three representative smart cities: Seoul, Songdo, and Sejong. The analysis traces how the governance model of each city changes throughout the three phases. According to stakeholders' roles and relationships, the governance model is categorized into four types (corporate, market, multilevel, and network governance). The governance model in all three cities showed little change. In Seoul and Songdo, market governance was dominant, while in Sejong, multilevel governance was. However, in phase 3, the institutional setting is changing to facilitate network governance in all three cities. The government guided the collaboration, giving more opportunities for private, academic, and civil actors to engage.